409 Serum Ca125 in patients with endometrial cancer. (18th September 2019) - Hashiguchi, Y; Yamauchi, M; Kasai, M; Fukuda, T; Ichimura, T; Yasui, T; Sumi, T
Abstract : Objectives: CA125 is one of the most widely used tumor markers in gynecological cancer including endometrial cancer. Although CA125 expression in endometrial cancer has been investigated, its prognostic value remains controversial. In this study, we investigated diagnostic and prognostic applications of serum CA125 for endometrial cancer. Methods: Between January 2006 and December 2012, serum CA125 levels were examined prospectively in 215 patients with endometrial cancer, and were then determined during treatment and at scheduled follow-up examinations in patients with elevated baseline serum CA125 levels. Results: During this period, a total of 215 patients (stage I, 142; stage II, 19; stage III, 32; stage IV, 22) were treated for endometrial cancer. The median age was 60 years (28–85), and histology types included 191 endometrioid carcinoma and 24 others. Subsequently 52 patients (24.2%) relapsed at the time of the last follow-up and the median follow-up time was 91 months (1–143). Elevated serum CA125 levels were identified in 69 patients (32.1%) and were associated with relapse of disease (p=0.005). Among the 69 patients with elevated serum CA125 levels, 56 (81.2%) achieved remission and serum CA125 levels returned to the normal range in all cases. There is no statistically significant relationship between an elevated CA125 levels and OS (p=0.06). Conclusions: Serum CA125 level seemed to be a potential prognostic indicator for endometrial cancer in clinical practice.